Implementation of STEAM-Based Educational Games and Changes in Elementary School Students’ Learning Interest in South Central Timor - Beti Istanti Suwandayani; Rr. Eko Susetyorini; Yus Mohammad Cholily; Baiduri Baiduri; Arina Restian; Kuncahyono Kuncahyono; Roimil Latifah (Sakura Digital Nusantara, 2026)
Purpose: This study examined changes in elementary school students’ interest in learning Mathematics and Science following the implementation of Science, Technology, Engineering, Arts, and Mathematics (STEAM)-based educational games in South Central Timor. Methods: This study employed a quantitative pre-experimental one-group pretest–posttest design. The participants comprised 90 students from grades I–VI at SD Inpres Besaloka, selected through total sampling. The intervention was implemented during two learning sessions. Data were collected using a five-point Likert-scale questionnaire measuring attention, interest, enjoyment, involvement, and willingness to participate in learning. Content validity was assessed through expert judgment, while instrument reliability was examined using Cronbach’s alpha. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test at a significance level of .05. Findings: Students’ mean learning-interest score increased from 65.42 (SD = 8.12) before the intervention to 84.78 (SD = 6.45) after the intervention, representing a mean difference of 19.36 points. The paired-samples t-test indicated a statistically significant difference between the pretest and posttest scores, t(89) = 18.74, p < .001. The magnitude of the difference was large, Cohen’s dz = 1.98. These findings indicate that students demonstrated higher learning-interest scores following the implementation of STEAM-based educational games. Research Implications: STEAM-based educational games may provide a relevant instructional alternative for supporting students’ interest in learning Mathematics and Science, particularly in resource-limited elementary school contexts. However, because this study employed a one-group pretest–posttest design without a control group, the observed changes cannot be attributed exclusively to the intervention. Further research should employ controlled experimental designs, longer intervention periods, and systematic observational measures. Originality: This study provides context-specific evidence regarding the implementation of STEAM-based educational games among elementary school students in a resource-limited region of Indonesia.